Gambaran Karakteristik Balita dengan Penyakit ISPA di Puskesmas Kanigaran Kota Probolinggo - Sholeh, Badrus; Juliningrum, Peni Perdani; Rahmawati, Ira (Pustaka Kesehatan, 2024)
Toddlers are included in the age group that is very susceptible to infections, especially infections that attack the respiratory tract. Acute respiratory infections (ARI) in developing countries are one of the factors that cause high mortality rates for children under five. This study aims to describe the characteristics of children under five with ARI disease in the working area of the Kanigaran Health Center, Probolinggo City. This research design used quantitative descriptive with a total sample of 146 medical record data. The sampling technique used a non-probability sampling technique with a quota sampling method. Collecting data using observation sheets. The results showed that under-fives with ARI were more common at the age of 1-3 years (71.2%), female gender (53.4%), non-LBW weight (88.4%), normal weight nutritional status (75.3%), and complete immunization status (57.5%). The characteristics of children under five in the Kanigaran Health Center Work Area, Probolinggo City are good. As a nurse, it was necessary to provide education to parents about preventing ARI, because currently ARI has attacked many toddlers with good characteristics.